Supply chain construction : the basics for networking the flow of material, information, and cash - Walker, William T. (Series on resource management., 2016)
"Emphasizing flexibility and strength, the book explores optimal ways to withstand product evolution, contingencies, organizational life cycles, and disasters for the long haul. Each chapter begins with a storyline describing the interpersonal relationships and intrapersonal conflicts that attend change. This is followed by a logical sequence of checklists, diagrams, maps, mathematical models, and spreadsheets for each topic. The author presents a 20-step blueprint that defines the supply chain network container and its product contents and includes example applications of the blueprint to nontraditional businesses found in small to medium-sized companies. He also includes decision factor charts for selecting the right suppliers, factories, and distributors; comprehensive examples of both forward and reverse supply chain network construction; and detailed explanations of inbound, midbound, and outbound logistics considerations."--